Understanding structure-activity relationships in linear polymer photocatalysts for hydrogen evolution - Michael Sachs (Nature Portfolio, 2018)
While inorganic semiconductors are well-studied for their solar-to-fuel energy conversion abilities, organic materials receive far less attention. Here, authors prepare linear conjugated polymers as H2 evolution photocatalysts and rationalize photocatalytic activities with fundamental properties.